The expression pattern, subcellular localization and function of three sterol 14α-demethylases in Aspergillus oryzae - Jin, Qi; Li, Ganghua; Qin, Kunhai; Shang, Yitong; Yan, Huanhuan; Liu, Hongliang; Zeng, Bin; Hu, Zhihong (Frontiers in Genetics, 2023)
Sterol 14α-demethylase catalyzes lanosterol hydroxylation, which is one of the key reactions in the biosynthetic pathway of sterols. There is only one sterol 14α-demethylases gene named Erg11 in Saccharomyces cerevisiae genome. In this study, three sterol 14α-demethylases genes named AoErg11A, AoErg11B and AoErg11C were identified in Aspergillus oryzae genome through bioinformatics analysis. The function of these three genes were studied by yeast complementation, and the expression pattern/subcellular localization of these genes/proteins were detected. The results showed that the three AoErg11s were expressed differently at different growth times and under different abiotic stresses. All of the three proteins were located in endoplasmic reticulum. The AoErg11s could not restore the temperature-sensitive phenotype of S. cerevisiae erg11 mutant. Overexpression of the three AoErg11s affected both growth and sporulation, which may be due to the effect of AoErg11s on ergosterol content. Therefore, this study revealed the functions of three AoErg11s and their effects on the growth and ergosterol biosynthesis of A. oryzae, which may contribute to the further understanding of the ergosterol biosynthesis and regulation mechanism in this important filamentous fungus, A. oryzae.